Implementation of Digital Image Steganography Application Using The Least Significant Bit Method Based on Android Via Telegram - Abdullah Muhajir; Muhamad Santoso; Bani Bani (Journal of Information System Research (JOSH), 2025)
Confidentiality and security of information on globalization is increasingly becoming a vital needs in various aspects of life. Any information would have a higher value if the concerning aspects of business decisions, security, or public interest. Where information-such information surely will be much sought after by various parties also have an interest in it. How to implement a data security system so that the data can be hidden in addition, can also be maintained in strict confidence from unauthorized parties. Designing applications Android-based steganography to hide documents by using the method of Least Significant Bit (LSB). This application can be expected to add to the knowledge of how to insert the document doc, xls, ppt, pdf and how to create application programs that can hide the document in the image, as well as developing the ability of the author to design the program mobile applications. The process of document confidentiality can be maintained this is due to the existence of the document is stored in a format that is different from the results of the prior encryption or already in the pasted file encryption is still the same.